(untitled) (Medico Legal Update, 2021)
Land-use systems are characterized by complex interactions between human decision-makers and their rights environment. Mismatches between the scale of human drivers and the impacts of human decisions potentially threaten the public rights as a whole. The research is a normative legal research using a statute, case, and conceptual approaches. The results show that land for management rights can be used for the purposes of conducting their duties or business, and its use can be transferred to third parties with the approval of the holder of management right. In fact, transfer of rights and imposition of mortgage rights can occur even without the permit of the holder of management right. However, when there is default, the creditor experiences obstacles because the National Land Agency rejects to issue a Land Registration Certificate without the holder’s permit of management rights, so that collateral cannot be executed. This condition results in the failure to fulfill the principles of justice and legal certainty for creditors and debtors. This provision should be abolished because it contradicts the principle of justice and legal certainty for the parties having an interest in utilizing the management rights land.